The winning of an olympic medal in modern pentathlon: New borders of sports sciences using an sportomics approach - Magno França, A.; Magalhães Neto, A. M.; Bachini, F.; Bassini, A.; Cameron, L. C. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: The modern pentathlon (MP) is an Olympic sport comprising the disciplines of fencing, swimming, horseback riding and an event combining running and pistol shooting. It becomes a great tool for studying the relationship between metabolic stress and the immune and central nervous systems. Our research focused on comparing Sportomics findings during MP training (Bassini and Cameron, 2014), bringing relevant changes in its planning content. The aim of this study is to describe metabolic adaptations of an exercise of various intensities using MP as a model. Methods: A female athlete was monitored for over 34 months, from years 2010-2013, during ten different weeks samples (3-6 days each), collected at fasting, pre and post training and after a 90 min recovery period. As result, training, her rest and nutritional behavior were adjusted. We measured ~300 blood and urine parameters. Results: We previously used the activity of creatine kinase (CK) to estimate exercise intensity (Bessa et al., 2008). During the first year, most of the training remained below a 300% increase (190-677 U/L) in CK levels. In the second year, the increase was near 400% (135-550 U/L), and it reached almost 800% (119-928 U/L) by year three. We were able to establish a pattern that returned the CK level to the near baseline values measured at the beginning of each week. In the last year, evolution in training showed that the increase in neutrophils decreased almost ten-fold with higher intensity exercise. The lymphocyte response was a third smaller than that for the neutrophils. Alanine aminotransferase raise in response to the increase in exercise intensity (peak at 350%), and it was smaller than that for aspartate aminotransferase (peak at 180%). In contrast, no changes in gamma-glutamyltransferase were measured and the modifications in training associated with diet and resting flattened the C-protein response, abolishing its increase even with higher exercise intensities. Discussion: Muscle injury markers and inflammatory response indicated the best recovery kinetics for diverse training phases. In addition, we showed that the increase in training intensity was followed by a decrease in inflammatory response without a lack in immunity. By monitoring these analyses, it is possible to adopt a more intense training program decreasing the chance of muscle injury. To our knowledge, this is the first biochemical and signaling analysis of a MP athlete, supported for the winning of an Olympic medal.